2007
DOI: 10.1111/j.1742-4658.2007.06074.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for specificities of reactivating factors for adenosylcobalamin‐dependent diol and glycerol dehydratases

Abstract: Diol dehydratase (1,2-propanediol hydro-lyase, EC 4.2.1.28) and glycerol dehydratase (glycerol hydro-lyase, EC 4.2.1.30) are isofunctional enzymes that catalyze adenosylcobalamin (AdoCbl) (coenzyme B 12 )-dependent conversion of 1,2-propanediol, 1,2-ethanediol, and glycerol to the corresponding aldehydes [1][2][3][4][5]. These enzymes encoded in the pdu (propanediol utilization) operon [6][7][8] and the dha (dihydroxyacetone) regulon [9][10][11][12], respectively, are involved in producing the electron accepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…We note that although the MeaI domain of Gk IcmF exhibits ATPase activity it is functionally distinct from the ATP-dependent chaperones for AdoCbl-dependent eliminases, e.g. diol dehydratases (36,37).…”
Section: Discussionmentioning
confidence: 85%
“…We note that although the MeaI domain of Gk IcmF exhibits ATPase activity it is functionally distinct from the ATP-dependent chaperones for AdoCbl-dependent eliminases, e.g. diol dehydratases (36,37).…”
Section: Discussionmentioning
confidence: 85%
“…Given the availability of the reduced metals and redox equivalents, many metallocofactors can “self-assemble” in vitro into their active form with varying degrees of success. However, recent studies from many groups have established the importance or essentiality of biosynthetic pathways for cluster insertion (1, 2) and have suggested the importance of repair or maintenance pathways (35) for regenerating active cofactors from damaged metal clusters. Pioneering studies of the Dean group (2), followed by work from many labs, have contributed to our understanding of iron-sulfur (FeS) cluster biosynthesis and the complex machinery required (reviewed in Reference 6).…”
Section: Introductionmentioning
confidence: 99%
“…Specific protein factors that are responsible for the reactivation of diol dehydratase [12][13][14] and glycerol dehydratase [15][16][17] were designated diol-dehydratase-reactivating factor and glycerol-dehydratasereactivating factor, respectively. They reactivate the inactivated holoenzymes by mediating the exchange of a damaged cofactor for intact AdoCbl through a molecular-chaperone-like mechanism [13,14,16,18]. Recently, we reported evidence for multiple turnovers with dioldehydratase-reactivating factor which demonstrated that the reactivating factor is an enzyme 'reactivase' [19].…”
Section: Introductionmentioning
confidence: 99%